Fetal autoimmune myocarditis and complete heart block – a case report - Murlewska, Julia; Szlagor, Magdalena; Respondek-Liberska, Maria (Prenatal Cardiology, 2021)
The patient was referred for fetal echocardiographic examination at 25.3 weeks of pregnancy due to bradycardia. Third-degree atrioventricular block was diagnosed, and hydroxychloroquine, steroid, and antibiotic therapy, as well as plasmapheresis, were started due to confirmation of the presence of antinuclear Ro-52 and Ro-60 maternal antibodies. The occurrence of disseminated focal areas of myocarditis was confirmed.